An initial study into the potential of wind farm control to reduce fatigue loads and extend asset life. Issue 2 (September 2020) - Harrison, Matt; Bossanyi, Ervin; Ruisi, Renzo; Skeen, Nick
Abstract: A quasi-static open loop wind farm control approach is considered, where optimisation is carried out offline in a simulation environment to create a lookup table of yaw setpoints implemented by a central wind farm controller. The objective of the optimisation is to reduce blade root bending moment for all turbines on the site, thereby increasing the asset life, and this is achieved by querying a fatigue loads database in DNV GL's LongSim software for wind farm control design, optimisation and verification. The Lillgrund 48-turbine layout is used for this example. The optimisation results in a small increase in annual energy production of 0.13% which is combined with a 0.4% increase in blade life, which is translated to an increase in asset life to yield a 0.5% increase in energy production over the farm lifetime. In this case we make the simplistic assumption that blades have the minimum life of all turbine components, and limit fatigue life. The results are a step towards wind farm control techniques which maintain and extend wind farm life, whilst simultaneously increasing energy production.